2010
DOI: 10.3945/ajcn.2009.27909
|View full text |Cite
|
Sign up to set email alerts
|

Lack of suppression of circulating free fatty acids and hypercholesterolemia during weight loss on a high-fat, low-carbohydrate diet

Abstract: Weight loss was similar between diets, but only the high-fat diet increased LDL-cholesterol concentrations. This effect was related to the lack of suppression of both fasting and 24-h FFAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 41 publications
1
52
0
6
Order By: Relevance
“…1). The latter triggers, at least if the amount of carbohydrate is sufficiently low (<60 g/day), an increase in fasting and postprandial NEFAs as well as ketone bodies [7]. The decrease in insulin can be predicted to decrease liver fat by diverting NEFA flux from lipogenesis to oxidation, although these processes have not been measured directly in humans [8].…”
Section: H-mrs Proton Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…1). The latter triggers, at least if the amount of carbohydrate is sufficiently low (<60 g/day), an increase in fasting and postprandial NEFAs as well as ketone bodies [7]. The decrease in insulin can be predicted to decrease liver fat by diverting NEFA flux from lipogenesis to oxidation, although these processes have not been measured directly in humans [8].…”
Section: H-mrs Proton Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…It has been observed that NEFA profiles in individuals with obesity or hyperlipidaemia are substantially altered compared with healthy individuals; such changes are regarded as an important risk factor for type 2 diabetes [7,9]. Palmitic acid is widely employed as a representative fatty acid to investigate the relationship between SFA and type 2 diabetes because it accounts for the highest percentage of dietary NEFA for the human body.…”
Section: Introductionmentioning
confidence: 99%
“…7 In contrast to reported positive health effects of carbohydrate restriction, increased free fatty acids and LDL cholesterol were observed in a recent experimental study. 8 From a long-term perspective, the health effects of carbohydrate-restricted diets are not well known. Increased all-cause, cardiovascular and cancer mortality demonstrated in cohort studies seem to contradict any sustainable benefit from a LCHP diet in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Increased all-cause, cardiovascular and cancer mortality demonstrated in cohort studies seem to contradict any sustainable benefit from a LCHP diet in the general population. 9 --12 Elevated LDL cholesterol as a result of carbohydrate-restricted diet 8 may contribute to atherosclerosis and CVD. Type of carbohydrates (for example, complex, simple) and proteins (for example, animal, vegetable) consumed may also affect risk associations.…”
Section: Introductionmentioning
confidence: 99%